Peran Self-Esteem sebagai Mediator pada Hubungan Parental Rejection dan Internet Gaming Disorder di Kalangan Remaja - Wijaya, Odilia Angeline Jofan; Soetikno, Naomi; Tiatri, Sri (GUIDENA: Jurnal Ilmu Pendidikan, Psikologi, Bimbingan dan Konseling, 2025)
Internet gaming is the recreational medium most commonly used by society today but it can be developed into one of the disorders with the term internet gaming disorder. It is noted that the prevalence of IGD among adolescents is 19.9% in England and 17% in China. Indonesia's media covers news of violations related to excessive internet gaming, including stealing, dropping out of school, causing fires, and stealing money from orphanages. One of the protective factors of IGD is the role of parents. Rejection from parents can have an impact on a person's low self-esteem. Lower self-esteem makes a person vulnerable to engage in risky behavior such as internet gaming disorder (IGD). This study aims to look at the role of self-esteem as a mediator in the relationship between parental rejection (PR) and indications of internet gaming disorder (IGD) among adolescents. This research is a correlational quantitative study with 116 participants aged 18-20 years, actively playing internet gaming in the past year, and having an IGD indication based on the cut-off score of the measuring instrument. PR was measured using the Adult Parental Acceptance-Rejection Questionnaire (Adult PARQ): Father and Mother-Short Form, self-esteem using the Rosenberg Self-Esteem Scale, and IGD using the Ten-Item Internet Gaming Disorder Test (IGDT-10). The research model uses the Process Macro statistical analysis. The results showed that parental rejection predicts the IGD, so the higher the rejection, the greater the IGD owned by the participants. In addition, self-esteem was not proven as a mediator in the relationship between parental rejection and IGD.